Factors contributing to exclusive breastfeeding amongst women of child bearing age at Sekhukhune District, Limpopo Province, South Africa - Makopo, T. D. (My University, 2020)
Background: Exclusive breastfeeding (EBF) is giving the infant no other food or drink apart from breast milk for the first six months of an infant’s life. Some women fail EBF due to poor latch, sore nipple, or breast engorgement which results in reduced breastmilk. Purpose: The aim of the study was to determine factors contributing to EBF amongst women of child-bearing age at Sekhukhune District. Study method: A quantitative study, applying the cross-sectional study design was used to conduct this study. Four-hundred and forty seven mothers with babies not greater than six months participated in the study. Ethical clearance and permission to conduct the study was obtained. A self-structured questionnaire was used to collect data. Data were analysed using Statistical Package for Social Sciences version 25 . Results: Most mothers (97%) attended antenatal care and only 3% did not attend. The rate of EBF was 55%. Mothers who initiated breastfeeding immediately after birth were 74%. Health care workers had a great influence on mothers to breastfeed exclusively (25%). Mothers who delivered vaginally were more likely to exclusively breastfeed. Conclusion: The findings of this study revealed the following factors which contributed towards EBF amongst women of childbearing age; such as attendance of antenatal care, counseling on feeding practices, mode of delivery, and the onset of breastfeeding after birth. Recommendations: Interventions such as counseling about the choice of feeding , education about the benefits of EBF, and starting with breastfeeding immediately after birth appears to be of importance in promoting EBF.
Thesis (M. A. (Nursing)) -- University of Limpopo, 2020
Keywords: Exclusive breastfeeding; Mothers; Feeding practices; Breastfeeding -- South Africa -- Limpopo; Breast milk